2011
DOI: 10.3892/mmr.2011.526
|View full text |Cite
|
Sign up to set email alerts
|

The set gene is a potential oncogene in human colorectal adenocarcinoma and oral squamous cell carcinoma

Abstract: Abstract. The purpose of this study was to determine whether set gene plays a role in the tumorigenesis of human colorectal adenocarcinoma and oral squamous cell carcinoma. We used the human colon carcinoma cell line Ls174 and oral squamous cell carcinoma cell line HSC3 to evaluate the effect of set suppression on cancer cell proliferation and apoptosis. Using real-time PCR, we examined set gene expression in human colorectal adenocarcinoma tissues and matched normal colorectal tissues. Thirty pairs of colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…I2PP2A (SET) and CIP2A, the endogenous inhibitors of PP2A, have been shown to be overexpressed in numerous cancer types [27] , [31] including chronic myelogenous leukemia [32] , cholangiocarcinoma [33] , colorectal and squamous cell cancer [34] , and neuroblastoma [35] . Amplification of the MYCN oncogene is the most important negative prognostic indicator in neuroblastoma [36] .…”
Section: Discussionmentioning
confidence: 99%
“…I2PP2A (SET) and CIP2A, the endogenous inhibitors of PP2A, have been shown to be overexpressed in numerous cancer types [27] , [31] including chronic myelogenous leukemia [32] , cholangiocarcinoma [33] , colorectal and squamous cell cancer [34] , and neuroblastoma [35] . Amplification of the MYCN oncogene is the most important negative prognostic indicator in neuroblastoma [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that SET upregulation, which leads to PP2A inhibition, is critical for BCR/ABL-positive cells to fulfill their tumorigenic potential (14). Recently, Jiang et al (6) reported that SET was overexpressed at the mRNA level in 21 tumor samples (70.0%) compared with the corresponding normal tissues. The results of the present study also identified that SET expression (at the mRNA level) in 31 patients was markedly increased in 70.9% of tumor specimens compared with adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…SET is critical for colorectal adenocarcinoma cell growth, since SET knockdown by specific siRNA results in significantly promoting apoptosis in vivo (6). Previously, Koldobskiy et al (28) showed that p53 is a tumor suppressor of which numerous mutations have been found in >50% of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SET is a multifunctional oncoprotein, involved in apoptosis, transcription, nucleosome assembly and histone binding, which ultimately promotes the initiation and progression of cancer. 4 The SET protein has two isoforms, which were named as isoform 1 and isoform 2, and both were potent inhibitors of protein phosphatase 2A (PP2A). 5 Overexpression of SET was characterized as being tumor-specific and was associated with the worse clinical outcomes in many human malignant carcinomas.…”
Section: Introductionmentioning
confidence: 99%